Ingeniería social: Análisis de las técnicas más utilizadas en los ataques a redes sociales y la percepción de la población urbana de Loja. - Guerrero Espinosa, Cristian Fabián (2024)
In an increasingly interconnected and constantly evolving digital environment, cyberspace has experienced exponential growth in the use of social networks, providing fertile ground for the propagation of cyber-attacks based on social engineering, understood as sophisticated psychological manipulation techniques that exploit users' trust and lack of knowledge. The lack of understanding of these techniques represents a significant threat to the security and privacy of online users, leaving both individuals and organizations exposed to serious risks, ranging from data leaks or sensitive information breaches to system intrusions and service outages, thus generating devastating and far-reaching consequences. The primary objective of this research is to thoroughly analyze the mechanisms of social engineering, evaluate its impact, and propose prevention and mitigation strategies. To this end, an exhaustive study was conducted that combined the analysis of case studies, user surveys, and a review of academic literature related to the topic, encompassing a multidisciplinary approach. This comprehensive investigation aims to bridge the gap between theoretical knowledge and practical application in the field of cybersecurity. The results of this research endeavor seek to contribute to scientific and practical knowledge about social engineering, laying the foundations for the development of training programs and technological tools that enable individuals and organizations to effectively protect themselves against such threats. By raising awareness of the dangers and prevention strategies, this work aspires to empower users and substantially enhance security in the ever-evolving digital environment, thereby promoting safer and more responsible use of information technologies. The findings also highlight the importance of continuous education and adaptive measures to keep pace with the rapidly changing landscape of cyber threats Keywords: Cybersecurity, cyberattacks, cybercrime, social networks, social media, cyberspace, social engineering.